Donor site complications of buccal mucosa harvesting in substitution urethroplasty - Ullah, Najeeb; Waleed, Ahmad; Shah, Syed Rafiuddin; Zubair, Agha Muhammad; Mustaf, Jamal; Hussain, Mushtaq (International Journal of Pathology, 2026)
Background: Buccal mucosa is commonly used as the graft of choice in substitution urethroplasty, but donor-site morbidity remains a relevant clinical concern. Evaluating the frequency and predictors of these complications is essential for improving postoperative outcomes. This study aimed to determine the frequency, types, and predictors of donor-site complications following buccal mucosa graft harvesting.Methods: It was a descriptive prospective study in 74 patients who had undergone buccal mucosa graft urethroplasty within a period of 12 months. Day 1-, 3- and 6-months Donor-site assessments were done. Clinical recording of complications was done. Independent t-tests, chi-square/Fisher exact tests and multivariate logistic regression were used as statistical analysis.Results: Donor-site complications occurred in 9 patients (12.2%). Edema was noted in 6 (8.1%), difficulty in mouth opening in 3 (4.1%), bleeding in 2 (2.7%), numbness in 2 (2.7%), chewing difficulty in 2 (2.7%), and infection in 1 (1.4%). Overall mouth opening showed minimal reduction, though patients with functional limitation experienced greater declines. Larger graft area (OR 1.12, p = 0.036) and diabetes (13 patients, 17.6%; OR 3.21, p = 0.045) were significant independent predictors of complications. Donor-site closure technique—open in 41 (55.4%) and primary closure in 33 (44.6%)—was not significantly associated with morbidity (p > 0.05).Conclusion: Buccal mucosa graft harvesting is safe and has low donor-site morbidity and most complications are mild and short-lived. One of the risk factors is the larger graft size and diabetes, which highlights the importance of careful graft planning and preoperative optimization.